Rapidly evolving composition of nebular infall recorded by magnesium isotopes in refractory inclusions - Haoyu Li; Ren T. C. Marquez; Gerrit Budde; Haolan Tang; Alexander N. Krot; Marina A. Ivanova; Johan Villeneuve; François L. H. Tissot (Proceedings of the National Academy of Sciences, 2026)
The 26 Al- 26 Mg systematics in calcium–aluminum-rich inclusions (CAIs)—the oldest known Solar System solids—has traditionally been used to provide high-resolution temporal constraints on the early Solar System evolution. More recently, the study of variations in the initial Mg isotope composition has emerged as a means to probe for potential compositional heterogeneity in the nascent solar nebula. Here, we report high-precision magnesium isotope data for a collection of 19 CAIs that captures the diversity of refractory inclusions. The data reveal widespread Mg isotope heterogeneity prior to 26 Al decay, covering a large range from −0.285 to +0.088‰. Combined with literature data, the distribution of Mg isotope heterogeneity in CAIs forms a continuum and no longer defines distinct populations. Our findings therefore suggest a continuous CAI formation process that captured a rapid temporal change in the composition of infalling material from the parental molecular cloud of the Solar System.